Hansa Pilsener : remaining relevant in a changing market - Oji, Chijioke; Beswick, Claire; Bick, Geoff ([London] : SAGE, 2016)
In September 2012, Khensani Nobanda took over as general manager of Hansa Pilsener, South African Breweries' (SAB) second-biggest brand. Under her predecessor, Mosidi Seretlo, SAB had developed a highly successful advertising campaign for Hansa, featuring a character named Vuyo who epitomised the positioning of the brand. Conditions in the beer market had changed since the campaign was first launched, however, and Nobanda was now considering options for the way forward. Should she move Hansa's communications campaign away from Vuyo, she wondered? Or change advertising agency for some new ideas?
Originally Published in: Oji, C., Beswick, C., & Bick, G. (2012). Hansa Pilsener: Remaining Relevant in a Changing Market. WBS-2012-6. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Hansa Pilsener (Firm); Brand name products -- Case studies; Branding (Marketing) -- Case studies; Advertising -- Case studies